Implementation of Environmental Educationto Support Sustainability of Green Campus Program in Universitas Riau - Suwondo, Suwondo; Darmadi, Darmadi; Haryanto, Rudy (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Education strategy through implementation of Environmental Education (EE) was implemented to achieve sustainability of green campus program in Universitas Riau. The learning process is done so that students have knowledge and attitude to applied in life. The research was conducted by survey method with measured parameters is the success rate of the learning process (planning, implementation and learning outcomes) and student attitudes toward the campus environment. Respondents are lecturers and students who have attended EE. Data were collected by observation, questionnaires, and documentation, which were analyzed descriptively. The results showed that the learning process of EE has a good with the students knowledge is good. The attitude of the students after attending the lecture also shows a good response to environmental management.